Design of Oligonucleotide Carriers: Importance of Polyamine Chain Length - Annenkov, Vadim V. (Polymers (Basel), 2018)
Amine containing polymers are extensively studied as special carriers for short-chain RNA (13–25 nucleotides), which are applied as gene silencing agents in gene therapy of various diseases including cancer. Elaboration of the oligonucleotide carriers requires knowledge about peculiarities of the oligonucleotide–polymeric amine interaction. The critical length of the interacting chains is an important parameter which allows us to design sophisticated constructions containing oligonucleotide binding segments, solubilizing, protective and aiming parts. We studied interactions of (TCAG)n, n = 1–6 DNA oligonucleotides with polyethylenimine and poly(N-(3-((3-(dimethylamino)propyl)(methyl)amino)propyl)-N-methylacrylamide). The critical length for oligonucleotides in interaction with polymeric amines is 8–12 units and complexation at these length can be accompanied by “all-or-nothing” effects. New dimethylacrylamide based polymers with grafted polyamine chains were obtained and studied in complexation with DNA and RNA oligonucleotides. The most effective interaction and transfection activity into A549 cancer cells and silencing efficiency against vascular endothelial growth factor (VEGF) was found for a sample with average number of nitrogens in polyamine chain equal to 27, i.e., for a sample in which all grafted chains are longer than the critical length for polymeric amine–oligonucleotide complexation.